TREATMENT OF ACID MINE DRAINAGE USING A SANDSTONE COLUMN - H. L. Yadav; A. Jamal (Rasayan Journal of Chemistry, c/o Dr. Pratima Sharma, 2017)
Acid mine drainage (AMD) or Acid rock drainage (ARD) from mining industry poses worldwide severe environmental problems including India also. In this study, heavy metal removal was tested in AMD samples collected from the Gorbi abandoned coal mine (India), having iron concentrations of 75 mg/L. Sandstone was collected from mine sites and converted into powders form and used as low-cost adsorbent in a column to treat acid mine drainage (AMD) obtained from the inactive Gorbi opencast coal mines (Singrauli coalfields, NCL). The pH value of the pit water sample improved from 2.48 to 3.90, along with the removal of, 100 % total iron, Lead (Pb), Cadmium (Cd), 71% of the electrical conductivity, 73% total dissolved solids and 50% of the salinity.
Keywords: Heavy metals, Sandstone Column treatment, and acid mine drainage